Feasibility and Efficacy of Function-Focused Care for Orthopedic Trauma Patients. Issue 3 (May 2016) - Resnick, Barbara; Wells, Chris; Galik, Elizabeth; Holtzman, Lauren; Zhu, Shijun; Gamertsfelder, Elise; Laidlow, Terry; Boltz, Marie
Abstract : To overcome challenges associated with optimizing function and physical activity among hospitalized older adults, we developed function-focused care for acute care (FFC-AC). The purpose of this study was to test the feasibility and preliminary effectiveness of this intervention. We hypothesized that hospitalized trauma patients exposed to FFC-AC would (1) maintain or improve function, spend more time in physical activity, and have fewer adverse events between admission and discharge; and (2) maintain or improve function, have less fear of falling, fewer depressive symptoms, less pain, be more physically resilient, and be less likely to experience adverse events at 1 month postdischarge compared with those exposed to FFC-education only (EO). FFC-AC was implemented by a research function-focused care nurse who worked on the participating units for 20 hr a week for 16 months to implement the three components of FFC-AC. The sample included 89 older orthopedic trauma patients the majority of whom were female ( N = 59, 66%), white ( N = 82, 92%), and not married ( N = 53, 59%). At discharge and/or 30 days postdischarge, participants in the treatment site showed greater improvement in function, less fear of falling, and better physical resilience when compared with those in the FFC-EO site. Future research is needed to continue to work on engaging staff in function-focused care approaches and optimizing the hospital environment and policies to support nurses in this type of care approach.